Occurrence and resistance profile of bacteria belonging to the ESKAPE group in hemodialysis patients - Ribeiro, Edlainny Araujo; Alves, Joicy Araújo Gomes; Alves , Krisly Ketelhyn Sousa (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Hemodialysis is the main treatment for patients with Chronic Renal Insufficiency and one of the main complications resulting from it is the occurrence of infections caused by opportunistic microorganisms belonging to the “ESKAPE” group. Aim: to determine the frequency of isolation of pathogens from the ESKAPE group and evaluate their respective antimicrobial resistance profiles in hemodialysis patients in a medium and high complexity hospital located in the Amazon. Outlining: Retrospective study carried out with collection of data available in the medical records of 167 patients diagnosed with Chronic Renal Insufficiency, undergoing hemodialysis or peritoneal dialysis from 2015 to 2019 in a regional hospital in the Southeast of Pará. Results: Of the 174 bacteriological cultures analyzed, 70.1% were positive and, of these, 57.4% were positive for bacteria belonging to the ESKAPE group. The most frequent microorganism belonging to the ESKAPE group was Staphylococcus aureus (47.1%); as to the resistance levels, 50% of Acinetobacter baumannii were resistant to carbapenems. Implications: The phenotypic profile of multidrug resistance to antimicrobials in strains of Acinetobacter baumannii was identified, highlighting the importance of knowledge about the profile of sensitivity to antimicrobials for a more assertive treatment and better prognosis.